2015
DOI: 10.1007/s11837-015-1452-2
|View full text |Cite
|
Sign up to set email alerts
|

Solidification in a Supercomputer: From Crystal Nuclei to Dendrite Assemblages

Abstract: Thanks to the recent progress in high-performance computational environments, the range of applications of computational metallurgy is expanding rapidly. In this paper, cutting-edge simulations of solidification from atomic to microstructural levels performed on a graphics processing unit (GPU) architecture are introduced with a brief introduction to advances in computational studies on solidification. In particular, million-atom molecular dynamics simulations captured the spontaneous evolution of anisotropy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 101 publications
(164 reference statements)
0
74
0
Order By: Relevance
“…(4.10) in which q ⊥ (φ) is replaced by q(φ). behavior [25,30]. Accurate results for the directional solidification of a columnar dendrite and free dendritic growth in the steady state can be obtained with this model as long as W is smaller than the dendrite tip radius divided by a constant of order unity.…”
Section: Nonvariational Model With Scalar Diffusivity (Nvs Model)mentioning
confidence: 94%
See 1 more Smart Citation
“…(4.10) in which q ⊥ (φ) is replaced by q(φ). behavior [25,30]. Accurate results for the directional solidification of a columnar dendrite and free dendritic growth in the steady state can be obtained with this model as long as W is smaller than the dendrite tip radius divided by a constant of order unity.…”
Section: Nonvariational Model With Scalar Diffusivity (Nvs Model)mentioning
confidence: 94%
“…The validity of this model was investigated in detail by carrying out convergence tests of the simulation results with respect to W. This model exhibits excellent numerical performance [25][26][27][28]. In particular, it has recently been shown that an accurate result (i.e., a well-converged result) for steady-state dendritic growth can be obtained with this model as long as W is smaller than the curvature radius of the dendrite tip divided by a constant of order unity [30].…”
Section: Introductionmentioning
confidence: 99%
“…Simulation studies including 2-D [9][10][11][12][13][14][15][16][17][18] and 3-D dendritic growth [2,[19][20][21][22][23][24][25][26][27] , dendritic growth of pure substances [9][10][11][19][20] , dendritic growth in binary alloys [1,[12][13][14][15][21][22][23][24][25] , and dendritic growth in multiple alloys [2,[16][17][18][26][27] have been reported. Multiple dendrites simultaneously grow during the casting process and their growth process can be directly simulated by using PFM [1,[28][29][30][31] . Mutual interactions and competitions exist among grains in the simultaneous growth of multiple grains.…”
Section: * LI Fengmentioning
confidence: 99%
“…As an open model, the phase-field model can be coupled with various external fields such as temperature, dissolution, gravity, and fluid fields, and can effectively combine the microscale with the macroscale. With the development of the phase-field model and improvements in computing technology, quantitatively simulating and predicting the microstructure in the phase transition of actual materials by using PFM has become the focus of research into this aspect of material structures [1][2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation